Impact of Tourism on Local Employment and Incomes in Three Selected Destinations: Case Studies of Sauraha, Nagarkot and Bhaktapur - Banskota, Kamal (Nepal Tourism and Development Review, 2013)
DOI: http://dx.doi.org/10.3126/ntdr.v2i1.7378 Nepal Tourism and Development Review Vol.2(1) 2012 1-31